Uji Kualitas Pupuk Organik Cair Kotoran Sapi dengan Beberapa Bioaktivator Terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium Ascalonicum L.) - Angelia Rachma Firdausy; Sugeng Winarso (Berkala Ilmiah Pertanian, 2023)
This study aims to improve the quality of cow manure liquid organic fertilizer from several bioactivators and to determine the effect of liquid organic fertilizer on the growth and yield of shallot (Allium ascalonicum L.) plants. This research was conducted on March 11 2022 – November 29 2022 at the cultivation land of Lamongan Regency. The research was arranged using Factorial RBD consisting of two levels and three replications. The first level is the types of bioactivators which consist of 5 types, namely without bioactivators (B0), Em4 (B1), BRE4 (B2), PAZ's (B3), and Mol rumen (B4). The second level is the concentration of liquid organic fertilizer to be tested on plants which consists of 4 concentrations of only basic fertilizer (K0), 20 ml/liter (K1), 40 ml/liter (K2), and 60 ml/liter (K3). Research data can be analyzed by ANOVA followed by Duncan's Multiple Range test at 5% level. The experimental results showed that a single treatment with the type of bioactivator helped improve the quality of liquid organic fertilizer for cow dung because the total N and pH parameters met the quality of the Minister of Agriculture. Single treatment concentration of cow manure liquid organic fertilizer showed a highly significant different effect on the variables observed in plant height, number of leaves, root volume, tuber diameter, and tuber dry weight. The variable number of tubers showed significantly different results in a single treatment, the concentration of cow dung liquid organic fertilizer and the fresh weight of tubers showed no significant differences. The best concentration of liquid organic fertilizer for cow dung was 60 ml/liter with the highest value at plant height 15.81 cm, number of leaves 10-11 leaves, root volume 10.96 ml, tuber diameter 1.86 cm, tuber number 38-38 tubers/plot, and tuber dry weight 17.89 grams. A significant correlation was also shown between fresh weight and tuber diameter because the value of r count 0.5237 was greater than r table 0.2144.